A High-Frequency Isolated Online Uninterruptible Power Supply (UPS) System with Small Battery Bank for Low Power Applications - Aamir, Muhammad; Tareen, Wajahat Ullah; Kalwar, Kafeel Ahmed; Memon, Mudasir Ahmed; Mekhilef, Saad (MDPI, 2017)
Uninterruptible power supplies (UPSs) are widely used to deliver reliable and high quality power to critical loads under all grid conditions. This paper proposes a high-frequency isolated online UPS system for low power applications. The proposed UPS consists of a single-stage AC-DC converter, boost DC-DC converter, and an inverter. The single-stage AC-DC converter provides galvanic isolation, input power factor correction, and continuous conduction of both input and output current. The low battery bank voltage is stepped up to high dc-link voltage by employing a high voltage gain boost converter, thus allows the reduction of battery bank to only 24 V parallel connected batteries. Operating batteries in parallel improves the battery performance and resolves the issues related to conventional battery banks that arrange the batteries in series combination. The inverter provides regulated output voltage to the load. A new cascaded slide mode (SM) and proportional-resonant (PR) control for the inverter has been proposed, which regulates the output voltage for both linear and non-linear loads. The controller shows excellent performance during load transients and step changes. Besides, the controller for boost converter and AC-DC converter is presented. Operating principle and experimental results of 1 kVA laboratory setup have been presented for the validation of proposed system.